2021
DOI: 10.1155/2021/6498451
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cavitation Evolution and Cavitation Erosion on Centrifugal Pump Blades by the DCM-RNG Method

Abstract: Cavitation can reduce the efficiency and service life of the centrifugal pumps, and a long-term operation under cavitation conditions will cause cavitation damage on the surface of material. The external characteristic test of the IS65-50-174 single-stage centrifugal pump was carried out. Moreover, the cavitation mechanism under specific conditions was analyzed by numerical simulation. Considering the macroscopic cavitation flow structure in the centrifugal pump, three different cavitation erosion prediction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In engineering, the point where the head drops by 3% is often taken as the critical point of cavitation to determine the operating range of centrifugal pumps. 16 Therefore, the critical NPSHa of the model pump is 1.57 m.…”
Section: Numerical Calculation Results and Analysismentioning
confidence: 99%
“…In engineering, the point where the head drops by 3% is often taken as the critical point of cavitation to determine the operating range of centrifugal pumps. 16 Therefore, the critical NPSHa of the model pump is 1.57 m.…”
Section: Numerical Calculation Results and Analysismentioning
confidence: 99%
“…The cavitation volume is reduced when cavity collapses, and the pressure wave is released. The erosive power function p pot can be defined as [ 25 , 27 – 30 , 33 , 35 , 36 , 40 , 46 ] where p is the pressure surrounding the vapor (Pa), p sat is the saturated vapor pressure (Pa), V vap is the vapor volume (m 3 ), V cell is the volume of the grid (m 3 ), α is the vapor volume fraction, and ε is the threshold.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…However, the adoption of such a solution requires the replacement of surface pumps with submerged pumps to stop the current descent and ascent of said surface pumps in the wells in order to bring them closer to the free surface of the water. Not only were the surface pumps not suitable, but they would also have broken down as a result of cavitation [27]. In addition, descent/ascent is a hard job, with a risk of falling.…”
Section: Surface Pumps Are Inappropriate For Extracting Water From Wellsmentioning
confidence: 99%
“…As mentioned above, these surface pumps should have been replaced by submersible solar pumps to allow for the safe and sustainable pumping of a water table that reached a depth of more than 12 m in the dry season. Pumping groundwater to a depth of more than 6 m leads to the cavitation (destruction of propellers) [27] of the pumps and their destruction (Figure 4). A survey 6 months after the end of the project revealed that 50% of the pumps were broken down.…”
Section: Difficulty Of Water Extractionmentioning
confidence: 99%